Short path first overlay building - WU Guo-fu; HAN Gang; DOU Wen-hua (Tongxin xuebao)
Shorter path first strategy to build topology matching overlay was presented.First,passive landmark based network distance prediction method was presented,and the network distance between peers could be predicted correctly with low overload and deployment cost.Then,table based diagonal space-filling curve map algorithm was presented,which could accelerate topology information selection.Finally,the process of building overlay using shorter path firs（SPF） strategy was described in detail.Experiment results shown that the SPF overlay can improve the topology matching remarkably.